Wittgenstein and analytic philosophy : essays for P.M.S. Hacker - Hacker, P. M. S. (Peter Michael Stephan); Glock, Hans-Johann, 1960-; Hyman, John (Oxford University Press, 2009)
Thirteen leading contributors offer new essays in honour of the eminent philosopher and Wittgenstein scholar Peter Hacker. They discuss issues in the interpretation of Wittgenstein, investigate central topics in the history of analytic philosophy, and explore and assess Wittgensteinian ideas about language, mind, action, ethics, and religion. - ;Peter Hacker is one of the most notable interpreters of Wittgenstein's work, a powerful and sophisticated exponent of Wittgensteinian ideas, and a distinguished historian of the analytic tradition. Thirteen leading philosophers and Wittgenstein scholar.